Archie Comics Digest Magazine NO.51 - Archie (US; Archie Comic Pub., 1981)
This collection of Jughead and Archie adventures, previously published in comic-book format, includes WISH FULFILLMENT, GIFT RIFT, and MUD BATH!
Keywords: Comic books, strips; Graphic novels